Pengaruh Lingkungan Yang Dimoderasi Oleh Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Pandemi Covid-19 - Dimas Satria Wibawa; Khomsiyah Khomsiyah (Owner : Riset dan Jurnal Akuntansi, 2022)
The objective of this study was to investigate the relationship between environmental performance and firm value as well as the relationship between environmental disclosure and firm value. The effect of each of these independent variables on the value of the company as well as the study's objective could also be moderated by the company size. There were 62 samples of companies that were listed on the Indonesia Stock Exchange between 2019 and 2021. Data analysis was examined by using multiple linear regression analysis with Moderate Regression Analysis method using SPSS 25 for further details. As a result, disclosure and environmental performance on firm value were significantly positive. Next, firm size as a moderator of firm value strengthens its effect, which was significant positive. Meanwhile, the effect of environmental performance did not moderate firm value.